Differences in the Platelet mRNA Landscape Portend Racial Disparities in Platelet Function and Suggest Novel Therapeutic Targets. Issue 3 (28th July 2021) - Garofano, Kaitlin; Park, C. Sehwan; Alarcon, Cristina; Avitia, Juan; Barbour, April; Diemert, David; Fraser, Claire M.; Friedman, Paula N.; Horvath, Anelia; Rashid, Kameron; Shaazuddin, Mohammed; Sidahmed, Alfateh; et al.
Abstract : The African American (AA) population displays a 1.6 to 3‐fold higher incidence of thrombosis and stroke mortality compared with European Americans (EAs). Current antiplatelet therapies target the ADP‐mediated signaling pathway, which displays significant pharmacogenetic variation for platelet reactivity. The focus of this study was to define underlying population differences in platelet function in an effort to identify novel molecular targets for future antiplatelet therapy. We performed deep coverage RNA‐Seq to compare gene expression levels in platelets derived from a cohort of healthy volunteers defined by ancestry determination. We identified > 13, 000 expressed platelet genes of which 480 were significantly differentially expressed genes (DEGs) between AAs and EAs. DEGs encoding proteins known or predicted to modulate platelet aggregation, morphology, or platelet count were upregulated in AA platelets. Numerous G‐protein coupled receptors, ion channels, and pro‐inflammatory cytokines not previously associated with platelet function were likewise differentially expressed. Many of the signaling proteins represent potential pharmacologic targets of intervention. Notably, we confirmed the differential expression of cytokines IL32 and PROK2 in an independent cohort by quantitative real‐time polymerase chain reaction, and provide functional validation of the opposing actions of these two cytokines on collagen‐induced AA platelet aggregation. Using Genotype‐Tissue Expression whole blood data, we identified 516 expression quantitative trait locuses with Fst values > 0.25, suggesting that population‐differentiated alleles may contribute to differences in gene expression. This study identifies gene expression differences at the population level that may affect platelet function and serve as potential biomarkers to identify cardiovascular disease risk. Additionally, our analysis uncovers candidate novel druggable targets for future antiplatelet therapies.